Personality factors and emotional Intelligence as predictors of frontline hotel employees’ emotional labour (2012)
The paper examined the influence of emotional intelligence and the big-five personality attributes on the performance of emotional labour of hotel frontline employees. A correlation design was adopted. Emotional labour was viewed as both multidimensional (deep acting and surface acting) and one-dimensional. A total of 145 frontline hotel workers, randomly selected from ten hotels within Ibadan, Nigeria, participated in the study. It was found out that hierarchical multiple regression analysis revealed that extraversion, neuroticism, and conscientiousness negatively predicted deep acting, extraversion positively predicted surface acting, while extraversion and neuroticism negatively predicted overall emotional labour. Emotional intelligence predicted deep acting and overall emotional labour. The research limitation was the fact that the study did not cover all possible personality attributes; also the dispositions needed for efficiency in other units of a hotel need to be investigated. This implies that hotel management should consider for employment into hotel frontline positions, applicants who have requisite dispositions on extraversion, neuroticism, and conscientiousness, and emotional intelligence. In addition, the training of frontline hotel workers should be tailored towards the behavioural dimensions of these personnel attributes. The study ventured into an uncommon area of human capital management in the hotel setting in Nigeria.